Analisis Kebutuhan Pengembangan Modul IPA Berbasis Etnosains Sumenep untuk Meningkatkan Literasi Sains dan Karakter Gotong Royong Peserta Didik - Nur Farida; Erlia Narulita; Iwan Wicaksono (Jayapangus Press, 2026)
Science learning at the junior secondary school level is expected to foster students’ scientific literacy and collaborative character in line with the Merdeka Curriculum. However, classroom practices still reveal a gap between these objectives and actual learning conditions. This article reports the needs analysis stage of a Research and Development (R&D) study employing the ADDIE model. The study aims to analyze the need for developing an ethnoscience-based science module grounded in the local context of Sumenep to support students’ scientific literacy and collaborative character. The needs analysis was conducted through a review of the junior secondary school science curriculum, semi-structured interviews with five science teachers, and questionnaires administered to 561 students from grades VII, VIII, and IX at SMP Negeri 1 Sumenep. The research instruments consisted of needs assessment questionnaires comprising nine items for students and eleven items for teachers. The questionnaires were developed based on scientific literacy indicators and collaborative character, validated through expert judgment, and demonstrated adequate reliability. Data were analyzed descriptively using mean scores and percentages. The results indicate that students experience difficulties in understanding science concepts, explaining scientific phenomena, and interpreting data and scientific evidence. In addition, science instruction has not been optimally integrated with local cultural contexts. Both teachers and students consistently expressed a strong need for contextual, collaborative, and ethnoscience-based science learning grounded in Sumenep local culture. The study concludes that developing an ethnoscience-based science module integrated with scientific literacy and collaborative character is necessary as a foundation for subsequent design and development stages.